Numerical methods for chemical engineering : applications in Matlab - Beers, Kenneth J. (Cambridge University Press, 2007)
Suitable for a first year graduate course, this textbook unites the applications of numerical mathematics and scientific computing to the practice of chemical engineering. The implementation of methods in MATLAB is integrated within each chapter and numerous examples in chemical engineering are provided.